Endoscopic resection using argon plasma coagulation for treating esophageal mucosal bridge in a patient with acquired immunodeficiency syndrome - Tae Hee Lee; Tae Hyong Kim (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Lee TH, Kim TH. Endoscopic resection using argon plasma coagulation for treating esophageal mucosal bridge in a patient with acquired immunodeficiency syndrome. Turk J Gastroenterol 2019; 30(8): 758-60.